Translation and cultural adaptation of the childbirth experience questionnaire - Al-Kubaisi, Muna Khaleel Dheyab; Al-Ani, Ali Sabri Radeef (2016)
The medical institutes are trying to offer maternity services to ameliorate the suffering through labour. Evaluating these services is partly reflected by the maternal satisfaction after labour. The childbirth experience questionnaire is a multi-dimensional instrument developed in Sweden in 2010. The questionnaire was proved to be useful in evaluating maternal satisfaction after childbirth. It was also translated and validated in the United Kingdom. The validated Malaysian version will be a new instrument in the medical institutes to evaluate the services offered to the community during childbirth.